2020
DOI: 10.1007/s13555-020-00469-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Experience and Laboratory Monitoring of Dupilumab in Patients with Moderate to Severe Atopic Dermatitis in a Tertiary Centre

Abstract: Introduction Dupilumab is a biologic therapy approved for treatment of moderate to severe atopic dermatitis (AD). Our objective was to assess the real-world effectiveness, safety and laboratory monitoring practices for dupilumab in a tertiary centre. Methods A retrospective review of medical records of all patients receiving dupilumab between September 2017 and October 2019 was undertaken. Eczema Area and Severity Index (EASI) and Dermatology Life Quality Index (DLQI) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
See 2 more Smart Citations
“…Real-world evidence of the effectiveness and safety of dupilumab for atopic dermatitis Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 (Ariëns et al, 2020, Ariëns et al, 2021, Faiz et al, 2019, Fargnoli et al, 2020, Fargnoli et al, 2019, Jang et al, 2020, Jo et al, 2020a, Kreeshan et al, 2021, Matsutani et al, 2020, Nettis et al, 2020b, Nettis et al, 2020c, Olesen et al, 2019, Patruno et al, 2021a, Patruno et al, 2021b, Quint et al, 2020, Ribero et al, 2020, Sears et al, 2020, Tauber et al, 2019, Uchida et al, 2021, Uchida et al, 2019. Patruno et al reported the effectiveness and safety of dupilumab in elderly patients with AD in real life (Patruno et al, 2021a, Patruno et al, 2021b.…”
Section: Effectiveness and Safety Of Dupilumab For Atopic Dermatitis In The Real Worldmentioning
confidence: 99%
“…Accumulating real-world evidence has ensured the effectiveness and tolerable safety of dupilumab both in the short term and in the long term. The articles searched in PubMed and Google Scholar are shown in Table 1 ( Ariëns et al., 2021 , 2020 ; Armario-Hita et al., 2019 ; Faiz et al., 2019 ; Fargnoli et al, 2020 , 2019 ; Ferrucci et al., 2020 ; Jang et al., 2020 ; Jo et al., 2020a , 2020b ; Kim et al., 2020 ; Kreeshan et al., 2021 ; Matsutani et al., 2020 ; Nettis et al., 2020b , 2020c ; Olesen et al., 2019 ; Patruno et al., 2021a , 2021b ; Quint et al., 2020 ; Ribero et al., 2020 ; Sears et al., 2021 ; Tauber et al., 2019 ; Tavecchio et al., 2020 ; Uchida et al., 2021 , 2019 ; Wang et al., 2020 ; Yamauchi et al., 2021 ). Patruno et al.…”
Section: Effectiveness and Safety Of Dupilumab For Ad In The Real Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the article by Kreeshan et al, which reported data on effectiveness and laboratory safety of dupilumab in a real-word cohort of 164 patients affected by atopic dermatitis (AD) followed over 12--30 weeks [1]. The authors reported that 58.96% of patients achieved at least a 75% improvement in eczema area severity index (EASI75), while 37.31% achieved EASI90 at 12-16 weeks.…”
Section: Commentarymentioning
confidence: 99%
“…Recent studies supported that after dupilumab treatment, patients who achieved clinical improvement in at least one of primary (EASI 75) or secondary (NRS peak pruritus improvement ≥4 or DLQI improvement ≥4) endpoints were considered to have experienced good therapeutic effects ( 16 18 ). Additionally, dupilumab has an acceptable safety profile, and does not require laboratory monitoring during the working period ( 19 ).…”
Section: Introductionmentioning
confidence: 99%